Management decision-making by leaders of small enterprises: analysis of basics and strategies - Shcharbinin, Siarhei N. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the analysis of rationalistic and strategic aspirations in management decision-making by actors of small business and the assessment of identified differences depending on the field of activity and the region. Managerial decision is presented as a specific kind of social interaction,integrating the intellectual and logical activity of actors with a behavioral component. The results of sociological research of small enterprises leaders as small business actors have been used as the basis for analysis. The research is aimed at analysis of decision-making activity, based on the assessment of entrepreneurs’ intentions regarding the management object. Directions and content of actions in decisionmaking (information assessment, use of improvement tools for decision-making (delegation, involvement of experts and staff), strategic orientation of functioning, application of selection criteria, attitude towards staff, partners and business associations, openness and readiness for changes) have been used as indicators for consideration. Dominating of rationalistic and strategic aspirations in managing small entrepreneurs has been substantiated. Leaders of small enterprises have been presented as rationally oriented participants of social interaction with the readiness to form a cohesive professional social group. The article discovers the content of decision-making process – search and selection of funds that meet set goals, aimed at implementing certain changes and achieving sustainable success. The practices of decision-making by entrepreneurs of different fields of activity and regions have been compared, as a result of which the conclusion about a relative homogeneity and absence of cardinal differences in its content has been made.
Keywords: managerial decision; small business; rationalistic and strategic aspirations; business environment; principle of management practice